Five-year experience of first-episode nonaffective psychosis in open-dialogue approach: Treatment principles, follow-up outcomes, and two case studies - Seikkula, Jaakko; Aaltonen, Jukka; Alakare, Birgittu; Haarakangas, Kauko; Keränen, Jyrki; Lehtinen, Klaus (Psychotherapy Research, 2006)
ABSTRACT : The open dialogue (OD) family and network approach aims at treating psychotic patients in their homes. The treatment involves the patient's social network and starts within 24 hr after contact. Responsibility for the entire treatment process rests with the same team in both inpatient and outpatient settings. The general aim is to generate dialogue with the family to construct words for the experiences that occur when psychotic symptoms exist. In the Finnish Western Lapland a historical comparison of 5-year follow-ups of two groups of first-episode nonaffective psychotic patients were compared, one before (API group; n?=?33) and the other during (ODAP group; n=42) the fully developed phase of using OD approach in all cases. In the ODAP group, the mean duration of untreated psychosis had declined to 3.3 months (p=.069). The ODAP group had both fewer hospital days and fewer family meetings (p<.001). Nonetheless, no significant differences emerged in the 5-year treatment outcomes. In the ODAP group, 82% did not have any residual psychotic symptoms, 86% had returned to their studies or a full-time job, and 14% were on disability allowance. Seventeen percent had relapsed during the first 2 years and 19% during the next 3 years. Twenty nine percent had used neuroleptic medication in some phase of the treatment. Two cases from both periods are presented to illustrate the approach.